Pelatihan Pembelajaran Daring Menggunakan Google Classroom Pada Guru-Guru di Provinsi Papua - Happy Lumbantobing; Ronaldo Kho; Bettisari Napitupulu; Ida Mariati Hutabarat; Jonner Nainggolan; Irfan Wahyudi; Martinus Y. Ruamba; Citra Ratna Napitupulu; Mindo Hotmaida Sinambela; Christine Mersi Rumpaisum (Universitas Pendidikan Muhammadiyah Sorong, 2023)
During the Covid-19 outbreak, the use of online learning presented a challenge for educators in the province of Papua. In Papua Province, 99 participants from 12 districts and cities participated in the training session utilizing Google Classroom. Training activities were carried out online using the zoom meeting application. The purpose of this training is to help and equip teachers to carry out online learning using the google classroom application. Participants were taught how to build classes, make announcements, create discussion forums, upload subject matter, assignments, and exam questions, construct quizzes and exam questions using google forms, and were given a simulation of how to utilize google classroom capabilities. The service's results suggest that users truly require training to advance their knowledge and abilities utilizing online learning tools like google classroom. After attending the training, participants have improved their knowledge and abilities in utilizing google classroom, have improved levels of creativity and expertise to create online courses, and have a high degree of satisfaction. Given that the Covid-19 pandemic is not known to have an end date and that the industrial revolution 4.0 and the industrial revolution 5.0 are both upon us, it is imperative that online learning training for teachers be conducted continually.